The Effect of Green Bond on Cumulative Abnormal Return and Abnormal Trading Volume in ASEAN Countries - Ratsameewongjan, Ausanee; Sanitthangkul, Joompoth; Puketkeaw, Konnut (วารสารนวัตกรรมธุรกิจ การจัดการ และสังคมศาสตร์, 2024)
The purpose of this research was to study the impact of the issuance of green bonds on cumulative abnormal returns and abnormal securities trading volume in ASEAN. The data was collected manually through media websites at the time the company announced the issuance of green bonds. The data also included financial information and comparison amongst other listed companies that did not issue green bonds from 2017-2021. The research used Event Study to analyze whether there was any cumulative abnormal return or any abnormal trading volume before the issuance of green bonds and after that. Pearson and multiple regression were used to analyze these correlations. The study showed that the issuance of green bonds did not increase cumulative abnormal returns or decrease abnormal trading volume. Therefore, it can be concluded that companies willing to increase their positive image on society and the environment could issue green bonds without taking extra precautions on cumulative returns and securities trading volume.